2007
DOI: 10.4161/cbt.6.9.4539
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and skin toxicity in cercopithecus aethiops sabaeus monkeys treated during 26 weeks with a high intravenous dose of the anti-epidermal growth factor receptor monoclonal antibody nimotuzumab

Abstract: Nimotuzumab (h-R3) is a humanized anti-epidermal growth factor receptor monoclonal antibody (mAb) registered for treating head and neck tumours. The present study was designed to evaluate the systemic and skin toxicity of chronic intravenous administration of the h-R3 in a relevant species demonstrated by comparing the h-R3 binding affinity constants (Kd) in microsomal placental fractions from Homo sapiens and Cercopithecus aethiops monkeys using an EGF-Receptor radioligand competition assay. The Kd obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Table 2 provides Kd of the different anti-EGFR monoclonals and the capacity of them to cause acneiform rash. 9 Cetuximab shows higher binding affinities than Nimotuzumab in human and in green monkey placentas. These results could be correlated with the dose-dependent skin toxicity effects observed at all dose levels with Cetuximab in a 39-week repeated-dose study in Cynomolgus monkeys.…”
Section: Functional Attributes Of Nimotuzumabmentioning
confidence: 99%
“…Table 2 provides Kd of the different anti-EGFR monoclonals and the capacity of them to cause acneiform rash. 9 Cetuximab shows higher binding affinities than Nimotuzumab in human and in green monkey placentas. These results could be correlated with the dose-dependent skin toxicity effects observed at all dose levels with Cetuximab in a 39-week repeated-dose study in Cynomolgus monkeys.…”
Section: Functional Attributes Of Nimotuzumabmentioning
confidence: 99%
“…In fact analysis show that higher affinity antibodies showed significantly higher skin toxicities. 43 Higher affinity antibodies may bind to antigen in the vicinity of the vessels increasing its toxic effects by reducing the penetration into the tumor. 44 Alternatively, as the model predicts, intermediate affinity antibodies (10 -8 and 10 -9 M) like Nimotuzumab would have maximum tumor uptake and minimum uptake in the normal tissues thereby reducing skin toxicity.…”
mentioning
confidence: 99%
“…17 Preclinical toxicological studies in relevant animal species have also demonstrated the low toxicity effect of Nimotuzumab when it was administered intravenously to monkeys or intracerebrally to rats. [18][19][20][21][22] Rhenium 188 (Re-188) from a tungsten-188/rhenium-188 (188W/ 188 Re)-radionuclide generator system, represents an attractive alternative radionuclide. Rhenium-188 (t1/2 = 16.9 h) is produced after the beta decay of the tungsten-188 parent (t1/2 69.0 d).…”
Section: Introductionmentioning
confidence: 99%